Psychological impact of coronavirus outbreak on borderline personality disorder from the perspective of mentalizing model: a case report - Chong, Seng Choi (Elsevier, 2020)
The coronavirus disease (COVID-19) is a global public health emergency (World Health Organization, 2020). Along with this outbreak is a parallel pandemic of fear, anxiety, and depression. The virus does not only affect physical health but also emotional well-being of all mankind, bringing substantial psychosocial impact on every member of the society. During this unprecedented outbreak, necessary measures had been taken to contain the virus transmission by mass indoor quarantine and social distancing. In Malaysia, movement control order has been implemented throughout the country as a containment measure battling this pandemic (Tang, 2020).